Investigation of cationic starch/Na-montmorillonite bionanocomposite adsorbent prepared by vibration milling for acid dye removal. (4th May 2017) - Kochkina, Nataliya E.; Skobeleva, Olga A.; Khokhlova, Yuliya V.
ABSTRACT: In this study, the low-cost powder bionanocomposite based on cationic starch (CS) and Na-montmorillonite (MMT) was obtained by the one-step procedure in a homemade vibration mill. The analysis of the bionanocomposite by x-ray diffraction (XRD) and thermogravimetric analysis (TGA) methods revealed that MMT had intercalated structure in CS matrix and the bionanocomposite possessed enhanced thermal stability as compared with that of pure CS. Adsorption capacity of CS/MMT bionanocomposite toward Acid Scarlet dye was evaluated as a function of initial dye concentration and contact time. The adsorption tests showed that the adsorption kinetics followed the pseudo-second order chemisorptions kinetic model. The adsorptions isotherms were best fitted using the three-parameter Sips model with the maximum adsorption capacity of 43.7 mg/g for CS/MMT bionanocomposite against 13.4 mg/g for CS.